Extracellular vesicle characteristics and microRNA content in cerebral palsy and typically developed individuals at rest and in response to aerobic exercise - Vechetti, Ivan J.; Norrbom, Jessica; Alkner, Björn; Hjalmarsson, Emma; Palmcrantz, Alexandra; Pontén, Eva; Pingel, Jessica; von Walden, Ferdinand; Fernandez-Gonzalo, Rodrigo (Frontiers in Physiology, 2022)
In this study, the properties of circulating extracellular vesicles (EVs) were examined in cerebral palsy (CP) and typically developed (TD) individuals at rest and after aerobic exercise, focusing on the size, concentration, and microRNA cargo of EVs. Nine adult individuals with CP performed a single exercise bout consisting of 45 minutes of Frame Running, and TD participants completed either 45 minutes of cycling (n=10; TD EX) or were enrolled as controls with no exercise (n=10; TD CON). Blood was drawn before and 30 minutes after exercise and analyzed for EV concentration, size, and microRNA content. The size of EVs was similar in CP vs. TD, and exercise had no effect. Individuals with CP had an overall lower concentration (~25%, P<0.05) of EVs. At baseline, let-7a, let-7b and let-7e were downregulated in individuals with CP compared to TD (P<0.05), while miR-100 expression was higher, and miR-877 and miR-4433 lower in CP compared to TD after exercise (P<0.05). Interestingly, miR-486 was upregulated ~2-fold in the EVs of CP vs. TD both at baseline and after exercise. We then performed an in-silico analysis of targets of miR-486 and identified the satellite cell stemness factor Pax7 as targeted by miR-486. C2C12 myoblasts were cultured with a miR-486 mimetic and RNA-sequencing was performed. Gene enrichment analysis revealed that several genes involved in sarcomerogenesis and extracellular matrix (ECM) were downregulated. Our data suggest that circulating miR-486 transported by EVs is elevated in individuals with CP and that miR-486 alters the transcriptome of myoblasts affecting both ECM- and sarcomerogenesis-related genes, providing a link to the skeletal muscle alterations observed in individuals with CP.